2021
DOI: 10.1111/biom.13569
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian multiple index models for environmental mixtures

Abstract: An important goal of environmental health research is to assess the risk posed by mixtures of environmental exposures. Two popular classes of models for mixtures analyses are response‐surface methods and exposure‐index methods. Response‐surface methods estimate high‐dimensional surfaces and are thus highly flexible but difficult to interpret. In contrast, exposure‐index methods decompose coefficients from a linear model into an overall mixture effect and individual index weights; these models yield easily inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…The factor analysis work of Ferrari et al noted above addresses this issue by using factor analysis to reduce the dimension of the exposure space [12]. McGee et al proposed another approach, BMIM, to address this weakness [5]. BMIM combines the strengths of existing exposure-index methods, such as weighted quantile sum (WQS) regression and qGc, by reducing the dimensionality of the exposure vector and estimating index weights with variable selection and treating these indices as inputs into the kernel regression framework.…”
Section: Estimation Of the Exposure-response Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The factor analysis work of Ferrari et al noted above addresses this issue by using factor analysis to reduce the dimension of the exposure space [12]. McGee et al proposed another approach, BMIM, to address this weakness [5]. BMIM combines the strengths of existing exposure-index methods, such as weighted quantile sum (WQS) regression and qGc, by reducing the dimensionality of the exposure vector and estimating index weights with variable selection and treating these indices as inputs into the kernel regression framework.…”
Section: Estimation Of the Exposure-response Surfacementioning
confidence: 99%
“…Relative potency factors-e.g., the Toxic Equivalency Factors (TEFs) of dioxin-like compounds-are one of the more familiar models of non-interaction/"additivity" in toxicology. One promising line of research connecting mixtures toxicology and epidemiology is the use of animal or in vitro data as priors for epidemiological studies using Bayesian methods such as BMIM [5].…”
Section: Toxicity and Related Chemical Informationmentioning
confidence: 99%
“…POP concentrations from this NHANES cycle are well characterized and have been used in prior environmental mixture analyses. 27 , 28 NHANES inclusion criteria have been reported previously. 29 For the chosen cycle, 11,039 participants were interviewed.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of "interaction" has been construed in many ways through different scientific fields 21 . For example, in current epidemiological studies, interactions are usually reported through association estimates of their effect sizes or inclusion probabilities [22][23][24][25][26][27][28][29][30][31][32][33] . Though estimating associations is essential, most methods do not provide any mechanistic or biological insight, possibly because the reported interactions are of particular functional forms (for example, multiplication of exposures) rather than representing their collective activities beyond certain concentration thresholds 34 .…”
Section: Introductionmentioning
confidence: 99%